A Survey on the Usage of Biomass Wastes from Palm Oil Mills on Sustainable Development of Oil Palm Plantations in Sarawak - Phang, K.; Lau, Shiew Wei (2017)
© Published under licence by IOP Publishing Ltd. As one of the world's largest palm oil producers and exporters, Malaysia is committed to sustainable management of this industry to address the emerging environmental challenges. This descriptive study aims to evaluate the oil palm planters' opinions regarding the usage of biomass wastes from palm oil mills and its impact on sustainable development of oil palm plantations in Sarawak. 253 planters across Sarawak were approached for their opinions about the usage of empty fruit bunch (EFB), palm oil mill effluent (POME), mesocarp fibre (MF), and palm kernel shell (PKS). This study revealed that the planters had generally higher agreement on the beneficial application of EFB and POME in oil palm plantations. This could be seen from the higher means of agreement rating of 3.64 - 4.22 for EFB and POME, compared with the rating of 3.19 - 3.41 for MF and PKS in the 5-point Likert scale (with 5 being the strongest agreement). Besides, 94.7 percent of the planters' companies were found to comply with the Environmental Impact Assessment (EIA) requirements where nearly 38 percent carried out the EIA practice twice a year. Therefore high means of agreement were correlated to the compliance of environmental regulations, recording a Likert rating of 3.89 to 4.31. Lastly, the usage of EFB and POME also gained higher Likert scale point of 3.76 to 4.17 against MF and PKS of 3.34 to 3.49 in the evaluation of the impact of sustainability in oil palm plantations. The planters agreed that the usage of EFB and POME has reduced the environmental impact and improved the sustainable development, and its application has been improved and increased by research and development. However the planters were uncertain of the impact of usage of biomass wastes with respect to the contribution to social responsibility and company image in terms of transparency in waste management.